A [trans] formação dos funcionários da educação básica em educadores e cogestores escolares - Santos, Ana Lúcia dos (2019)
This research developed in the research line of Management in Networked Educational Technologies is part of Graduate Program in Networked Educational Technologies (PPGTER), from Federal University of Santa Maria (UFSM), in the Area of Concentration of Educational Technologies in Network for Education Innovation and Democratization, aiming to investigate if there is a change of action of the students of a distance education course (DE) in the scope of the Professional. The research analyzed the potentialities of development of the protagonism and emancipation of the subjects involved, through observation of activities in the Virtual Learning Environment (AVEA), questionnaires and audiovisual recording with student reports. Participants in this study are school officers, students of the Technical Course on Didactic Multimedia offered by the Federal Institute Farroupilha. The study is based on reflections on the training of education officers,in virtual education and in the epistemology of pedagogical mediation in DE, from authors such as Baumann, (2010); Consani, (2008); Demo, (1999); Monlevade (2005); Moreira, (2016); Morin, (2000); Primo, (2007); Josso, (2004; 2009); Kenski, (2013); Freire, (1983; 1979; 1997; 2005); in dialogue with the General Guidelines Manual - Brazil, (2009; 2014; 2017), among others. With the analysis of the praxis of educational actions mediated by networked educational technologies, we evidence the Professional Program and the de as potentializers of action change in school officers who become educators and co-managers. As a finalresult of the research a video / documentary was produced. We understand the importance of research dissemination for information disclosure and that other professionals in the area may, perhaps, use this production.